Assessment of Lodz Province Residents Opinions on the Needs For the Social Activation of Seniors - Kopiec, Tomasz; Stańczyk, Katarzyna; Burzyńska, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
Lodz is characterized by the highest advancement of the aging process and the highest values of negative health measures in the country. This results in the necessity to undertake intensive, multi‑sectoral and coherent actions towards the elderly, also in the area of activation. The aim of the study was to assess the opinion among Lodz Province residents on the needs for the social activation of seniors. 235 inhabitants of the Lodz Province took part in the survey conducted in 2020. The research tool was an anonymous questionnaire, made available on‑line. The statistical analysis used structure indicators, measures in the field of descriptive and analytical statistics – the correlation coefficient, the χ2 independence test and the Mann‑Whitney U test. More than ⅓ of the respondents considered artistic classes to be the most attractive classes dedicated to seniors, every 4. mentioned workshops in the field of information technology. Nearly half of the respondents indicated fairs and intergenerational events as the most important events activating seniors. 8 out of 10 respondents saw the need to initiate intergenerational integration activities. Residents of larger cities indicated a higher frequency of participation of seniors in dedicated events than people living in villages and smaller towns (p < 0.05). As barriers to using senior services, the inhabitants of larger cities most often mentioned the lack of information, and the remaining respondents – problems with transport (p < 0.05). The need to initiate activities integrating generations and classes educating seniors in the area of new technologies was confirmed. Increasing digital competences among older people could contribute to increasing their independence, and thus improve the quality of life of seniors and their careers.